2019
DOI: 10.1097/cej.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

The detection of interval colorectal cancers following screening by fecal immunochemical test may predict worse outcomes and prompt ethical concerns: a 6-year population-based cohort study in a full district

Abstract: The rates of colorectal cancer (CRC) interval surveyed in screen-detected patients using a fecal immunochemical test (FIT) are not negligible. The aim of this study was to assess the effect of interval cancer on outcomes compared with a population with cancer diagnosed after a positive test result. All patients between 50 and 71 years of age, who were residents of the Mantua district, affected by CRC and operated on from 2005 to 2010 were reviewed. Other than patient-related, disease-related, and treatment-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Idigoras et al [ 26 ] reported a 5-year survival rate of 90.1% in screen-detected group, 76.3% in interval group and 60.5% in non-uptake group (P = <0.001). Corrado et al [ 29 ] found an average overall survival in non-uptakers of 60.5%, whereas for participants, the overall survival was 85.1% (P = 0.001). Among the participating subjects, patients with interval cancers had worse overall survival rates (68.5%) than patients with screen-detected cancers (87.0%, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Idigoras et al [ 26 ] reported a 5-year survival rate of 90.1% in screen-detected group, 76.3% in interval group and 60.5% in non-uptake group (P = <0.001). Corrado et al [ 29 ] found an average overall survival in non-uptakers of 60.5%, whereas for participants, the overall survival was 85.1% (P = 0.001). Among the participating subjects, patients with interval cancers had worse overall survival rates (68.5%) than patients with screen-detected cancers (87.0%, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour location was classified as right side (from the cecum to the transverse colon), left side (from the splenic flexure to the sigmoid colon) or rectum [ 8 , 9 , 18 ]. Differentiation grade was classified as well-differentiated (grade 1), moderately differentiated (grade 2) and poorly/undifferentiated (grade 3–4) [ 8 , 14 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The importance of investigating ICs became clear when several studies described varying FIT-IC proportions between 6.9% and 50.8% (24-month invitation interval and FIT-positivity thresholds between 10 and 80 lgHb/g). 7,9,[11][12][13] In addition, ICs are associated with more severe outcome and reduced chances of survival, 9,14 which is substantiated by the strong relation between tumour stage and survival. In Flanders (2011-2015) the five-year survival for CRC in the general population was 96% for tumournode-metastasis (TNM) stage I CRC compared with 19% for stage IV CRC.…”
Section: Introductionmentioning
confidence: 99%